Evidence for elevated psychiatric distress, poor sleep, and quality of life concerns during the COVID-19 pandemic among U.S. young adults with suspected and reported psychiatric diagnoses. (October 2020) - Liu, C.H.; Stevens, C.; Conrad, R.C.; Hahm, H.C.
Highlights: Individuals with psychiatric diagnoses are vulnerable to distress during COVID-19. Those with a suspected diagnosis also reported greater psychiatric distress. Those with prior mental health concerns reported more grief and worry. Those with prior mental health concerns reported poorer sleep and functioning. Having a psychiatric diagnosis was associated with greater psychiatric distress. Abstract: We report distress levels and functional outcomes based on self-reported pre-existing mental health conditions among U.S. young adults ( N =898) during the COVID-19 pandemic (April 13-May 19, 2020). Depression, anxiety, and PTSD symptoms, as well as COVID-19-related concerns, sleep problems, and quality of life were compared across the following pre-existing mental health groups: 1) no diagnosis, 2) suspected diagnosis, 3) diagnosed and untreated, and 4) diagnosed and treated. Compared to those without a diagnosis, the likelihood of scoring above the clinical threshold for those with a diagnosis - whether treated or not - was more than six-fold for depression, and four-to six-fold for anxiety and PTSD. Individuals with a suspected diagnosis were 3 times more likely to score above the clinical threshold for depression and anxiety and 2 times more as likely to score above this threshold for PTSD compared to those with no diagnosis. We also present higher levels of COVID-19-related worry and grief, poorer sleep, and poorer reported health-related quality of life among those with either a suspected or reported mental health diagnosis. Findings provide evidence of vulnerability among individuals with a mental health diagnosis or suspected mental health concerns during the initial weeks of the COVID-19 pandemic.